UZBEKISTAN - LAND OF RICH CULTURAL HERITAGE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article delves into the rich cultural heritage of Uzbekistan, situated at the crossroads of history in Central Asia. From the ancient Silk Road cities of Samarkand, Bukhara, and Khiva to lesser-explored regions like the Fergana Valley and Nurata, Uzbekistan offers a captivating blend of architectural marvels, artistic traditions, and warm hospitality. The narrative unfolds with a focus on iconic landmarks, culinary delights, and authentic cultural encounters, inviting travelers to embark on a journey that celebrates the enduring legacy of this fascinating country. Through exploration and immersion, Uzbekistan emerges as a destination where history, tradition, and modernity converge to create an unforgettable travel experience.